Superparamagnetic Iron Oxide as an Efficient Catalyst for the One-Pot, Solvent-Free Synthesis of 5,5-Disubstituted Hexahydropyrimidines and Their Spiro Analogues - Fatemeh Janati; Majid M. Heravi; Ahmad Mirshokraie (Journal of Chemistry)
Superparamagnetic Fe3O4 is shown to act as a very efficient catalyst for the one-pot, three-component synthesis of 5,5-disubstituted hexahydropyrimidines and their spiropiperidines. The catalyst is easily recovered by the use of an external magnet and reused in several reactions without any noticeable loss of activity. The products are obtained in short time and good purity upon separation of the catalyst and evaporation of the volatiles of the reaction mixture.